Reduction-sensitive fluorescence enhanced polymeric prodrug nanoparticles for combinational photothermal-chemotherapy - Zhang, Yuanyuan (2020)
In this study, a reduction-sensitive supramolecular polymeric drug delivery system was developed for combinational photothermal-chemotherapy of cancer. The multifunctional system was self-assembled by specific host-guest interactions between hydrophilic β-cyclodextrin functionalized hyaluronic acid and adamantane linked camptothecin/dye conjugate, where a near-infrared (NIR) absorbing dye IR825 was loaded. The hydrophilic hyaluronic acid shell endows the assembly with excellent colloidal stability and biocompatibility. The embedded disulfide bond in the camptothecin/dye conjugate was cleaved under reducing environment, leading to the release of the conjugated drug and the recovery of fluorescence emission. Meanwhile, the dye IR825 could efficiently transfer the absorbed light into local heat, making the nanoplatform an effective system for photothermal therapy. As evident by confocal microscopy images, the nanoplatform was quickly internalized by HeLa, MCF-7, and U14 cancer cells and released drug molecules inside the cells. In vitro cell viability assays confirmed that the cancer cells were efficiently killed by the treatment of the nanoplatform under NIR light irradiation. Significant tumor regression was also observed in the tumor-bearing mice upon the administration of the nanoplatform through combinational photothermal-chemotherapy therapy. Hence, this nanoplatform presented a great potential in site-specific combined photothermal-chemotherapy of tumor.